Therapeutic CD154 antibody for lupus: promise for the future? - Kelsoe, Garnett (American Society for Clinical Investigation, 2003)
Systemic lupus erythematosus (SLE) is a prototypical systemic autoimmune disease characterized by the production of pathogenic autoantibodies. A new study demonstrates that passive antibody specific for the TNF family member, CD154, ameliorates disease by reducing levels of self-reactive antibody in the serum. This study demonstrates a substantial potential for anti-CD154 antibody in the treatment of humoral autoimmunity.